Hubungan antara Faktor Sosiodemografi dan Personal Hygiene dengan Kejadian Skabies di Pondok Pesantren - Putri Maharani Salsa Bilatussalama; Hanna Tabita Hasianna Silitonga; Mellyanawati; Minarni Wartiningsih (Jurnal Syntax Admiration, 2025)
Scabies or scabies disease is a skin disease caused by the Sarcoptes scabiei mite which is characterized by symptoms of 4 cardinal signs. Transmitted through direct or indirect contact, can occur in densely populated environments and poor personal hygiene and sanitation. This study aims to determine the relationship between sociodemographic factors and personal hygiene with the incidence of scabies at the Ngalah Islamic boarding school, Pasuruan. This is a quantitative observational analytical study with a case control approach. The number of samples used was 64 respondents using the simple random sampling method. Primary data were obtained from questionnaires and interviews which showed that most respondents were in the case group with male gender (75.0%) and poor personal hygiene (81.3%). based on the Chi-Square statistical test <0.005 which means there is a significant relationship between sociodemographic factors and the incidence of scabies. However, the sleeping habits variable got the Chi-Square test results> 0.005, namely there was no significant relationship between sleeping habits and the incidence of scabies. In male gender and poor personal hygiene causes a person to have a high risk of being exposed to scabies skin disease.